Biomimetic 3D bioprinted bilayer GelMA scaffolds for the delivery of BMP-2 and VEGF exogenous growth factors to promote vascularized bone regeneration in a calvarial defect model in vivo - Alarcin, Emine; Akguner, Zeynep Puren; Ozturk, Ayca Bal; Yasayan, Gokcen; Ilhan-Ayisigi, Esra; Kazan, Aslihan; Guner, F. Seniha (Elsevier, 2025)
The effective treatment of critical-sized bone defects requires a coordinated interaction between osteogenesis and angiogenesis. Inspired by natural bone tissue, we developed a bilayer vascularized bone construct using extrusion-based dual 3D bioprinting. The construct consists of two layers: a bone-mimetic layer, which includes highly methacrylated gelatin (GelMAHIGH), hyaluronic acid, alginate, osteoblast cells, and bone morphogenetic protein-2 (BMP-2) loaded polylactic-co-glycolic acid (PLGA) nanoparticles; and a vessel-mimetic layer, composed of low methacrylated gelatin (GelMALOW), alginate, endothelial cells, and vascular endothelial growth factor (VEGF)-loaded PLGA nanoparticles. These layers were designed to form hierarchical microstructures that enable sustained release of growth factor (GF) thereby stimulating both osteogenic and angiogenic processes. The nanoparticles were synthesized using a microfluidic platform, achieving a narrow size distribution. The hydrogel bioinks were systematically optimized for printability, and it was found that incorporation of nanoparticles improved their mechanical properties, surface roughness, degradability, and GF release profiles. Notably, GF release followed zero-order kinetics, ensuring consistent delivery over time. The bilayer scaffolds demonstrated superior cell proliferation and spreading compared to single-layer scaffolds, and in vivo experiments showed enhanced repair of calvarial bone defects. These findings highlight the significant clinical potential of bilayer scaffolds with sequential GF delivery for treating critical-sized bone defects.
Keywords: Controlled growth factor release; 3D bioprinting; Bone scaffold; Bilayer scaffold; Vascularization; Bone regeneration